Numerical investigation of quad rotors in ground effect - Tanabe, Y.; Sugawara, H.; Sunada, S.; Yonezawa, K.; Tokutake,H. (My University, 2021)
Flowfield and performance of quad rotors hovering in ground effect (IGE) are investigated through numerical simulations. A variable pitch-controlled quadrotor drone developed for applications in severe gusty circumstances is modeled in the simulations. Compared with a single rotor, the flowfields around the quad rotors are highly complex. The change of rotor performance with the height from the ground is noticeably different comparing to the single rotor case. The required power for a constant thrust does not monotonically decrease with the rotor height, which adds difficulties to the stable flight control near the ground. Comparisons to the quadrotor drone with a central fuselage are also performed. Remarkable differences in the flowfield and rotor performance are found.